Peningkatan Kemampuan Membaca Permulaan Menggunakan Metode struktural Analitik Sintetik Berbantu Media Gambar dikelas ll SDN 36/ VI Rantau Panjang lll - Juwairiah Juwairiah; Reni Guswita; Randi Eka Putra (CV. Master Literasi Indonesia, 2025)
This research is based on observations conducted on July 16-17, 2025, in grade II of SDN 036/VI Rantau Panjang. It was found that there were problems in the learning process of students who were unfamiliar with letters and had difficulty distinguishing letters with similar shapes, were unable to combine letters into words, and the use of ineffective learning methods and media in grade II of SDN 036/VI Rantau Panjang.This study was a Classroom Action Research (CAR) conducted in two cycles consisting of four meetings, each cycle consisting of four stages: planning, action, observation, and reflection. The results of this study show the process and outcomes of Indonesian language learning in grade II of SDN 036/VI Rantau Panjang, with 22 students, including 13 boys and 9 girls. Details of teacher observations in cycle I showed an average of 67%, categorized as fairly good, and in cycle II, 87%, categorized as very good. The results of student observations in cycle I with a percentage of 50% are in the poor category, while in cycle II 82% are in the good category. The results of student learning in cycle I are 56% with poor criteria and do not reach KKTP, in cycle II 79% are in good criteria and reach KKTP. And it is concluded that the use of synthetic analytical structural methods assisted by image media can improve the ability to read Indonesian language learning